O sonho de Descartes: o homem das paixões - Briganti, Carlos Rosario (2006)
This dissertation is an audacious proposal to closely examine the personality of René Descartes which could perhaps, lead us to a theory about his mission in life which is intimately fused with his philosophy. The complexity of his psyche as revealed by his first biographer Baillet is expressed in the progression of his writings. We have chosen our course of direction from one of the higher points selected from the Cartesian philosophical work: the development of a human being incorporating his passions. René Descartes was a man enamored with the truth and for this very reason he merged highly powerful statements, doubts, biases, flights of fantasy and deviations, of which conventional man is incapable. René Descartes was a man who inspired hope: a better future for mankind, without concern merely in relation to his own future. It is impossible to classify René Descartes as an atheist, Catholic, Protestant, libertine or laborer. This classification task is an impossible one because each biographer has imbued his own particular interests in their works at that time. We know all knowledge acquired is linked to a one s own peculiar cause which is also the case in relation to biographers. Descartes himself was to a great extent responsible for these widely disparate viewpoints since his own accomplishments in this world were exactly as he had described his life in his childhood diary, confined within a shrouded world. The period in history was horrifying and all those who dared contradict the Catholic dogmatic order were persecuted. The group of servile yes men and accomplices were by far greater in number and permeated society at the time. This left René Descartes with little choice but to employ masks to enable him to at least continue living. The Catholic dogmas could not be contradicted under threat of punishment by the Inquisition. René Descartes nevertheless conducted his life much like Hegel would write in his definition of the role of the hero and thereby he endeavored and managed to restore philosophy to it rightful place among research, reflection and wisdom. René Descartes wrote his most fundamental text, the Discurse de la Metode (Discourse on Method) in French. This extraordinary event was founded on the right of all people to acquire knowledge, especially women. This uncommon and libertine attitude is just one of the facets of this man, who based on his own freedom to act and think, at no time adhered to any system, school of philosophy or politics; nor did he allow anything to stand in the way of his being truly free. He was very much aware that his attitude would fuel the fires of the moralists from whom anything can be expected or from the cynics who deprive themselves of nothing that is not self serving. His philosophical project in life was enormous; metaphysics comprising the roots of this philosophical tree while the trunk represents physics sucking up the sap running from the roots branching in to the leafy boughs of Mechanics, Medicine and Morals. The project of an integrated human being is intimately connected to Medicine, Ethics and Morals, constituting the Cartesian project. The other project of making nature understandable in the light of reason which edifies science is as he writes in a letter to his friend, Farther Mersenne: Physics dissipates the celestial myths proffered by the poets and painter, which keep God occupied opening and closing the gates to the winds, spilling dew on the flowers and launching lightening bolts against the rocks. Descartes in relation to his reflections and writings in the Discourse of Method, under the fear of its creation, replicates one of the masks, thus writing: do not speak of this to anyone (...) expose the subject as if it were a sample of your philosophy (...) hidden behind the painting to hear to what to say. Our attempt was to endeavor to understand this Cartesian path, conducting hypothetical interpretations about the Descartes´ dream, which according to our fanciful interpretation reveals the paths chosen by Descartes, his fears to be respected, some of the pain he was subjected to but particularly in regard to his defamation. We are aware of and privileged to hold Our interpretation fantasies and leave the texts themselves intact, to survive our comments.